2017
DOI: 10.18632/oncotarget.18924
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200c increases radiosensitivity of human cancer cells with activated EGFR-associated signaling

Abstract: MicroRNA-200c (miR-200c) recently was found to have tumor-suppressive properties by inhibiting the epithelial-mesenchymal transition (EMT) in several cancers. miR-200c also interacts with various cellular signaling molecules and regulates many important signaling pathways. In this study, we investigated the radiosensitizing effect of miR-200c and its mechanism in a panel of human cancer cell lines. Malignant glioma (U251, T98G), breast cancer (MDA-MB-468), and lung carcinoma (A549) cells were transfected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…Overexpressing miR-200c is reported to inhibit invasion, migration, and vascular tube formation of malignant glioma, breast cancer, and lung carcinoma cells. And these phenotypic changes are associated with EphA2 downregulation 26 , furthermore, miR-200a is demonstrated to direct repress EphA2 oncogene in triple-negative breast cancer cells 27 . MiR-26b can also inhibit cell proliferation, migration, and invasion by targeting EphA2 in hepatocellular carcinoma cells 28 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overexpressing miR-200c is reported to inhibit invasion, migration, and vascular tube formation of malignant glioma, breast cancer, and lung carcinoma cells. And these phenotypic changes are associated with EphA2 downregulation 26 , furthermore, miR-200a is demonstrated to direct repress EphA2 oncogene in triple-negative breast cancer cells 27 . MiR-26b can also inhibit cell proliferation, migration, and invasion by targeting EphA2 in hepatocellular carcinoma cells 28 .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported that miRNAs can regulate EphA2 in cancer cells 26 - 28 . Overexpressing miR-200c is reported to inhibit invasion, migration, and vascular tube formation of malignant glioma, breast cancer, and lung carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Another study found that miR-200c prevented the invasion and migration of glioblastoma by activating EGFR pathways that reversed the epithelial–mesenchymal transition in glioblastoma. 36 Intriguingly, due to the homology in seed sequences, miR-200c and miR-141 share the same target, ZEB1, which is known to inhibit glioma cell growth and migration. 37 However, recent studies obtained inconsistent results.…”
Section: Mir-200 and Metastasis Of Gliomasmentioning
confidence: 99%
“…One study demonstrated that miR-200c increases glioma cell radiosensitivity by activating EGFR-associated signaling. 36 …”
Section: Effect Of Mir-200 On Chemotherapeutic and Radiotherapeutic Rmentioning
confidence: 99%
See 1 more Smart Citation